Pengaruh Pembelajaran Berbasis Masalah dengan Penilaian Diri terhadap Efikasi Diri dan Hasil Belajar Mahasiswa - Gusti Ayu Mahayukti; Putu Kartika Dewi; I Gusti Nyoman Yudi Hartawan (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2020)
The aim of this research was studying whether problem based learning with self assestment affect student self efication and their learning outcome. The population of this research is student of mathematics education department, Sciences Fakulty of Undiksha academic year 2019/2020. The post test only control group design was used for this experimental design. The questioner and test were used gahthering the data, which valid. It’s data the analyzed by using MANOVA. The research showed that silmutaneously there weren’t deference self efication and leaning outcome of differencial calculus between student who learned by problem based learning with self assestment and who learned by conventional learning. But, the analyzed of student worksheet was showed that 83.43% failed in solving HOTS problem in expereiment group, and the other group failed 83.41%. In addition, the results of the open questionnaires related to the use of PBM with self-assessment showed positive results, namely that 87.88% of students said they were happy with PBM with self-assessment, and only 12.12% stated that they were not happy because they had not been able to do their own assessments.